Myeloid/lymphoid neoplasms with FGFR1 rearrangement. Issue 7 (3rd July 2018) - Strati, Paolo; Tang, Guilin; Duose, Dzifa Y.; Mallampati, Saradhi; Luthra, Rajyalakshmi; Patel, Keyur P.; Hussaini, Mohammad; Mirza, Abu-Sayeef; Komrokji, Rami S.; Oh, Stephen; Mascarenhas, John; Najfeld, Vesna; et al.
Abstract: Myeloid/lymphoid neoplasms with FGFR1 rearrangement are a rare entity. We present a multicenter experience of 17 patients with FISH-confirmed FGFR1 rearrangement. The clinical presentation at diagnosis included myeloproliferative neoplasm (MPN) in 4 (24%) patients, acute leukemia (AL) in 7 (41%), and concomitant MPN with AL in 6 (35%). The two most frequently observed cytogenetic abnormalities were t(8;13)(p11.2;q12)(partner gene ZMYM2 ) and t(8;22)(p11.2; q11.2)( BCR ). Seventy-eight percent of tested patients had a RUNX1 mutation, of whom all had AL. Overall response rate to frontline therapy was 69%, and 76% of patients subsequently received allogeneic stem cell transplant (ASCT). After a median follow-up of 11 months, median progression-free survival was 15 months and median overall survival was not reached. In conclusion, FGFR1 -rearranged hematologic malignancies present with features of MPN and/or AL. FGFR1 and RUNX1 are therapeutic targets for ongoing and future clinical trials.